The prognostic value of the direct bilirubin to albumin ratio in critically ill patients with cirrhosis: Insights from MIMIC-IV database - XingYi Yang; Guangdong Wang; Zhang Min; LiHong Lv; Ji Yang (PLoS ONE, 2025)
Background Patients with severe cirrhosis are at a higher risk of mortality. This study aimed to investigate the association between the direct bilirubin-to-albumin ratio (DBAR) and 28-day mortality in critically ill cirrhotic patients using data from the publicly available MIMIC-IV database. Methods This study explores DBAR’s relationship with 28-day mortality in severe cirrhosis patients. We first conducted univariate and multivariate analyses to identify independent risk factors. Then, we used Kaplan-Meier (KM) survival analysis to assess DBAR’s link with survival time and created KM curves. DBAR’s predictive accuracy was evaluated using Receiver Operating Characteristic (ROC) analysis, and the relationship was examined using restricted cubic spline modeling and subgroup analyses. Result This study enrolled 509 cirrhotic patients with in-hospital and ICU mortality rates of 22.3% and 14.3%, respectively. Univariate and multivariate analyses revealed a significant association between DBAR and 28-day mortality risk, with a hazard ratio of 1.16 (95% CI: 1.10–1.24, p < 0.001), confirming DBAR as an independent risk factor for short-term prognosis. DBAR demonstrated good predictive accuracy for 28-day mortality (AUC = 0.702, 95% CI: 0.650–0.753). Patients were divided into low-risk (DBAR < 4) and high-risk (DBAR ≥ 4) groups, with the high-risk group showing a hazard ratio of 3.05 (95% CI 1.87–4.97, p < 0.001) after multivariate adjustment. Restricted cubic spline (RCS) analysis identified a nonlinear relationship between DBAR and 28-day prognosis (p-Nonlinear = 0.022, p < 0.001). Subgroup analysis showed no interaction between DBAR and most subgroups. Conclusion The DBAR scoring system offers an efficient and user-friendly approach for assessing prognosis in critically ill cirrhotic patients.